Optimizing the Effectiveness of Memorandums of Understandings through Omnichannel Marketing Strategies: Insights into Innovation and Sustainability in Sri Lankan Higher Education Partnerships - Dilogini, S. (Wayamba University of Sri Lanka, 2024)
This research aims to investigate the application of omnichannel marketing technology in the improvement of memorandums of understandings for Sri Lankan universities and professional institutions specializing in business, management, and marketing. Evaluating the role of omnichannel marketing technologies in the context of innovation and sustainability, the research seeks to address the research gap lies in the lack of empirical studies exploring how omnichannel marketing strategies can optimize the effectiveness of memorandums of understandings in Sri Lankan higher education partnerships, particularly in enhancing visibility, engagement, and sustainability. The study employs a qualitative content analysis approach to analyze ten MOUs, focusing on the role of omnichannel marketing in web content, social media posts, and other advertisements to enhance the effectiveness of higher education partnerships in Sri Lanka. The objectives involving cooperation goals, marketing networks, and audience are examined to state, how these strategies enhance the relationship between universities and professional organizations as innovation and sustainability in higher education partnerships. Omnichannel marketing technologies facilitate interaction and sustainability as they make content more innovative, effective for the audience and visible. In this vein, the study identifies that the joint marketing awareness that involves co-branding in content and the use of pooled resources aligns the strengths of the universities and professional institutions in the realization of MOUs. Using personal pages in social networks, emails, sites, blogs, and live meetings, it is possible for the Sri Lankan universities and organizations to attract the potential learners, enhance partnership, and foster program implementation. From the research, such strategies are found to be instrumental in fostering sound strategic partnerships that foster sustainable and competitive forms of practice in HEPs. Future research should explore cross-country comparisons and longitudinal studies to validate findings and refine strategies.
Keywords: Higher Education Partnerships; Innovation; Memorandums of understanding; Omnichannel marketing; Sri Lankan universities; Sustainable practices